School-based social skills group training (SKOLKONTAKT™): a pilot randomized controlled trial - Fridell, Anna; Coco, Christina; Borg, Anna; Bölte, Sven (Frontiers in Psychology, 2023)
Purpose Differences in socio-communicative behaviors contribute to social challenges for autistic learners at school and, in turn, are associated with increased risks of educational underachievement, social exclusion, and mental health issues. Given that intervention delivery in natural contexts may enhance skills generalization, build support capacities in society, and have practical advantages for youth and families, SKOLKONTAKT™ has been adapted from the clinically based social skills group training KONTAKT™ for mainstream educational settings to mitigate these risks. Methods A pilot, randomized controlled trial with active controls was conducted in a mainstream Swedish high school. Autistic learners and students with social skills challenges (N = 33; MAGE = 17.5) were randomized to SKOLKONTAKT™ (n = 17) or active control (n = 16). Efficacy was measured at post and follow-up (3 months) on social skills [Social Skills Group Assessment Questionnaire (SSGQ); primary outcome] by parent-, self-, and (masked) teacher-report as well as self-reported life quality and social goal attainment. Results Despite COVID-19 challenges, 70.6% (n = 12) completed SKOLKONTAKT™, and 87.5% (n = 14) completed control groups. SKOLKONTAKT™ improved on a series of items on SSGQ as well as subjective life quality beyond controls. A larger proportion of social goals were attained, and side-effects were of little impact and proportionally fewer in SKOLKONTAKT™. Conclusion SKOLKONTAKT™ is a safe, feasible, and promising intervention option for autistic learners in mainstream educational settings. A larger-scale study is desirable to confirm the effects identified in this pilot study.